Socialization and Training on the Use of Augmented Reality Applications for Teachers in Paciran Village to Make English Learning Easier - Authar, Nailul; Djuwari, Djuwari; Aquariza, Novi Rahmania; Zaniar, Savira (UKInstitute, 2024)
This community service attempts to explore the use of augmented reality (AR) in how teachers in Paciran can be well known to introduce new vocabulary to students right there. This is a qualitative study with the data taken from both surely by distributing the questionnaires both to the students and the teachers. The questionnaires to the students concern the use of AR in their learning of English while the questionnaires to the teachers is related to the use of AR in their schools and the teachers’ engagement in this AR for their classes. The data is also taken from the interview to the English teachers about the use of AR in learning English. Sifter all the data triangulated from the students and the teachers, they will be decoded and determined into the themes. Besides that, they are also presented in tables. Finally, the inferences can be done for making the conclusion. Based on the results of the training and application experiments to students, each teacher and student agreed that AR media had a positive impact on English learning.